ETLINGERA GENUS: PHYTOCHEMICAL SCREENING AND ANTICANCER ACTIVITY - Wahyuni Wahyuni; Ajeng Diantini; Mohammad Ghozali; Sahidin Sahidin (Jurnal Farmasi Sains dan Praktis, 2021)
Etlingera is one of the plant genera from the Zingiberaceae family and is widely distributed in Asia to the Pacific Islands, with various species ranging from 150 to 200 species. The Etlingera are commonly used as spices, vegetables, and traditional medicines. Many pharmacological activities have been reported from this genus, including antioxidants, antibacterials, cholesterol-lowering, anticancer, and others. The phytochemical content of Etlingera reported are phenolics, diarylheptanoids, flavonoids, steroids, alkaloids, and terpenoids. Eight species from Etlingera, namely Etlingera elatior, E. pavieana, E. brevilabrum, E. pyramidosphaera, E. megalocheilos, E. coccinea, E. fimbriobracteata, and E. corneri are reported provided anticancer activity. This review article aims to review the phytochemical screening from Etlingera genus, and its anticancer activity.